Navigating the Research Landscape: An In-Depth Analysis of Challenges Encountered by Public and Private Medical and Dental Undergraduate Students: Navigating the Research Landscape - Qamar, Wajiha; Nisar, Anita (Pakistan Journal of Health Sciences, 2023)
Understanding the challenges experienced by undergraduate students in different educational environments is crucial for navigating the evolving research landscape effectively. Objective: To review the challenges faced by undergraduate students enrolled in public and private sector dental and medical colleges in Khyber Pakhtunkhwa, Pakistan's. Methods: The study used a cross-sectional design and a tailored questionnaire that was distributed to undergraduate students in both sectors to gather data. Time limits, knowledge and research abilities, the availability of mentoring and training, institutional support, and language difficulties were covered by the questionnaire. The chi-square test and descriptive statistics were used to analyse the data. Results: Key findings include research engagement is low, particularly in the private sector. Time restrictions are a significant barrier that are particularly severe in the private sector. Significant barriers include a lack of research abilities and information, as well as inadequate mentoring and training programs. Particularly in the public sector, there is a dearth of institutional support. Language obstacles are typically not very severe. The chi-square test confirms a significant difference in challenges between public and private sector students. Conclusions: Both public and private sectors have low levels of research engagement, with the private sector having a larger non-participation rate. Both students in the public and private sectors encounter significant challenges, with private sector students identifying time restraints and a lack of information and research skills as the most significant barriers. Lack of readily available mentorship and training programs, as well as institutional support, is a significant barrier for students in both sectors.